Hydrolyzed Fat Formula Increases Brain White Matter in Small for Gestational Age and Appropriate for Gestational Age Neonatal Piglets - Caputo, Megan P.; Williams, Jennifer N.; Drnevich, Jenny; Radlowski, Emily C.; Larsen, Ryan J.; Sutton, Bradley P.; Leyshon, Brian J.; Hussain, Jamal; Nakamura, Manabu T.; Kuchan, Matthew J.; Das, Tapas; Johnson, Rodney W. (Frontiers in Pediatrics, 2020)
Background. Intrauterine growth restriction is a common cause of small for gestational age (SGA) infants worldwide. SGA infants are deficient in digestive enzymes required for fat digestion and absorption compared to appropriate for gestational age (AGA) infants, putting them at risk for impaired neurocognitive development. Objective. The objective was to determine if a hydrolyzed fat (HF) infant formula containing soy free fatty acids, 2-monoacylglycerolpalmitate, cholesterol, and soy lecithin could increase brain tissue incorporation of essential fatty acids or white matter to enhance brain development in SGA and AGA neonatal piglet models. Methods. Sex-matched, littermate pairs of SGA (0.5-0.9kg) and AGA (1.2-1.8kg) 2 day old piglets (N=60) were randomly assigned to control (CON) or HF formula diets in a 2 x 2 factorial design. On day 14, 24 piglets were used for hippocampal RNA-sequencing; the rest began a spatial learning task. On days 26-29, brain structure was assessed by magnetic resonance imaging (MRI). Cerebellum and hippocampus were analyzed for fatty acid content. Results. SGA piglets grew more slowly than AGA piglets, with no effect of diet on daily weight gain or weight at MRI. HF diet did not affect brain weight. HF diet increased relative volumes of 7 brain regions and white matter (WM) volume in both SGA and AGA piglets. However, HF did not ameliorate SGA total WM integrity deficits. RNA sequencing revealed SGA piglets had increased gene expression of synapse and cell signaling pathways and decreased expression of ribosome pathways in the hippocampus compared to AGA. HF decreased expression of immune response related genes in the hippocampus of AGA and SGA piglets, but did not correct gene expression patterns in SGA piglets. Piglets learned the T-maze task at the same rate, but SGA HF, SGA CON, and AGA HF piglets had more accurate performance than AGA CON piglets on reversal day 2. HF increased arachidonic acid (ARA) percentage in the cerebellum and total ARA in the hippocampus. Conclusions. HF enhanced brain development in the neonatal piglet measured by brain volume and WM volume in specific brain regions; however, more studies are needed to assess long-term outcomes.